Shepherd school as a tool for the empowerment of the livestock sector - Ruiz Morales F.A.; Ureña Cámara L.P.; Leal Muñoz C.; Arrebola Molina F.A.; Sayadi S.; Camacho M.E.; Ortiz Berrocal F.; Cruz Moriana V. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Grazing as a basis for feeding flocks is declining in the European Union. Different problems related to the access of the land and the hardness of the shepherd’s work, among others, have meant that the number of farms with this model have dropped. Andalusia (Spain) created its Shepherd School in 2010, an initiative based on collaboration between different entities in the field of livestock and environment. The figure of the shepherd teacher is fundamental for the success of the school: during six weeks, the students carry out practices with them in their farms. In total, there are eighty-four active shepherd teachers, with different local breeds and flocks with different types of production: meat, milk and cheese making. The Shepherds School changes its location in each edition, locating in areas where extensive livestock farming and environmental aspects (protected areas, forests, mountain areas ...) are important. Normally, all the agents of the livestock sector interact in different activities: round tables, workshops with students, group visits, child activities, etc. The media (television, radio and press) regularly visit the school, which is an opportunity to show a sustainable, professional and innovative sector.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)